Influence of Brand Equity and Movieliking can Override Impact of Misleading Brand Placement toward Brand Attitudes - Afiff, Adi Zakaria; Furi, Westi Noria; Metroprawiro, Denyza Wahyuadi (The South East Asian Journal of Management, 2014)
The starting point of this study is the phenomenon termed misleading brand placement, a condition found where the brand placement in a movie depict the brand in a time where the brand has not yet exist, providing the brand an older age. As the brand used in the brand placement is a brand with high brand equity, the combination of older age and high brand equity is suspected to give a higher evaluation of the brand. To test these suspicions, 3 experiments were conducted to see the influence of consumer knowledge of the misleading brand placement, brand equity and movie liking toward the brand attitude. The results show that when consumers do not have knowledge of the misleading brand placement they are not affected by misleading brand placement; but when they know of the misleading brand placement, brand attitude tend to be still be high when brand equity is high; and finally, when brand equity is high, a positive movie liking can further strengthen brand equity in reducing the negative effect of the misleading brand placement.